Cyclin B/CDK1 and Cyclin A/CDK2 phosphorylate DENR to promote mitotic protein translation and faithful cell division - Katharina Clemm von Hohenberg; Sandra Müller; Sibylle Schleich; Matthias Meister; Jonathan Bohlen; Thomas G. Hofmann; Aurelio A. Teleman (Nature Communications, 2022)
The cell cycle regulates translation during mitosis by controlling DENR stability. Here, the authors show the non-canonical translation initiation complex DENR·MCTS1 is phosphorylated during mitosis by CDK1 and 2, enabling the translation of genes needed for proper mitotic progression.